2012
DOI: 10.4236/jwarp.2012.410102
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between Multi-Layer Perceptron and Radial Basis Function Networks for Sediment Load Estimation in a Tropical Watershed

Abstract: Prediction of highly non-linear behavior of suspended sediment flow in rivers has prime importance in environmental studies and watershed management. In this study, the predictive performance of two Artificial Neural Networks (ANNs), namely Radial Basis Function (RBF) and Multi-Layer Perceptron (MLP) were compared. Time series data of daily suspended sediment discharge and water discharge at the Langat River, Malaysia were used for training and testing the networks. Mean Square Error (MSE), Normalized Mean Squ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(22 citation statements)
references
References 24 publications
2
19
1
Order By: Relevance
“…Predicted BY= 0.67×BY+32e+03 (3) Predicted Y = 0.53×Y + 1.5e+03 (4) Overall, according to R 2 , the best model for prediction of BY and Y was MLP model using the equations of 3 and 4. This finding was in agreement with Memarian and Balasundram (2012) who reported that the MLP model showed a slightly better output than RBF network model in predicting suspended sediment discharge, especially in the training process.…”
Section: Prediction Of Biological Yield and Yield Of Barley Using Mlrsupporting
confidence: 92%
See 1 more Smart Citation
“…Predicted BY= 0.67×BY+32e+03 (3) Predicted Y = 0.53×Y + 1.5e+03 (4) Overall, according to R 2 , the best model for prediction of BY and Y was MLP model using the equations of 3 and 4. This finding was in agreement with Memarian and Balasundram (2012) who reported that the MLP model showed a slightly better output than RBF network model in predicting suspended sediment discharge, especially in the training process.…”
Section: Prediction Of Biological Yield and Yield Of Barley Using Mlrsupporting
confidence: 92%
“…Among various methods of ANN and learning algorithms, multi-layer perceptron networks (MLP), and radial basis function (RBF) are the most popular neural network models. One of ANN applications is in agriculture science (Heinzow and Richard, 2002;Memarian and Balasundram, 2012). In the past years there has been an increasing interest in ANN modeling in different fields of agriculture, particularly for some areas where conventional statistical modeling failed.…”
Section: Introductionmentioning
confidence: 99%
“…Clearly, all networks (S1 -S5) showed weak robustness in estimating sediment load with a large magnitude, especially for records higher than 4000 ton/day. Such a limitation in ANN application has also been reported by Hsu et al (1995), Morid et al (2002), Talebizadeh et al (2010) and Memarian and Balasundram (2012). Inefficiency of the ANN -GA model in estimating large magnitudes of sediment load can be attributed to different non-linear relationships governing the process of sediment detachment and final sediment load generated from a watershed.…”
Section: Scenariomentioning
confidence: 92%
“…Some case studies (e.g. Mustafa et al [10], Memarian and Balasundram [20]) employ only discharge or rainfall as the input. There are no other reasons besides data unavailability.…”
Section: Datamentioning
confidence: 99%